THE INFLUENCE OF ANTICIPATORY GUIDANCE HEALTH EDUCATION ON THE ROLE OF PARENTS IN PREVENTING INJURIES IN SCHOOL-AGE CHILDREN (6-12 YEARS) IN SUMBER JENON MALANG TOURISM - ANA KHUMAIDITA PUTRI; Rahmawati Maulidia; Puguh Raharjo (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: Injury is the impact of an external agent that causes physical or mental damage. The purpose of this study was to determine the effect of anticipatory guidance health education on the role of parents in injury prevention. This research is a Pre-experimental quantitative research with the type of One group pretest-s posttest design with a cross sectional approach. The study sample was parents who had school-age children determined by the probability sampling method , namely simple random sampling. The instrument used is a questionnaire on the role of parents in injury prevention. Methods: The data analysis method using the Wilcoxon Rank Sum test showed that the results of the pretest were 87% (42 respondents) obtained moderate results and the posttest was known to 95.8% (46 respondents) obtained high results. Objectives: The results of bivariate statistical tests in this study obtained the results of p = (0.000) < (0.05) which means that there is an influence of anticipatory guidance health education on the role of parents in preventing injuries in school-age children (6-12 years), Results: then for the standard value (Z) is -6.412 where the value is -1.645 It is found that the value of Z calculate > Z table which is -6.412 > -1.645 so that Ha is accepted which means there is also an influence of anticipatory guidance health education. Conclusions: From the results of this study, health education influences parents on the incidence of injury in children. The health education provided has an influence on parents in preventing injuries